Âzyk sovremennoj russkoj pressy: sociolingvističeskij aspekt - Lysakova, Irina P. (Stylistyka, 2021)
The author shows the connection between the language and style of the press and the social conditions of its functioning and the typological features of the edition. The article offers the methodology of sociolinguistic analysis of newspaper with respect to its orientation towards its audience.The typological features of the language model of the edition are found in headings, titles and the body of the text. The stylistic unity of the heading, the tytle and the text contains the semantic code of the edition and marks the level of the joumalists' professionalism.